Sharp and blunt force trauma concealment by thermal alteration in homicides: An in-vitro experiment for methodology and protocol development in forensic anthropological analysis of burnt bones. (June 2017) - Macoveciuc, Ioana; Márquez-Grant, Nicholas; Horsfall, Ian; Zioupos, Peter
Highlights: Non-human bones were subject to sharp and blunt force trauma, followed by burning. Sharp and blunt force trauma signature were not entirely masked by heat exposure. In these burnt specimens, it was possible to trace the origin of the trauma impact. Emphasis is placed on future standardization of fracture experimentation in burnt bone. Promotes the use of anthropologists in the recovery of human remains at fire scenes. Abstract: Burning of human remains is one method used by perpetrators to conceal fatal trauma and expert opinions regarding the degree of skeletal evidence concealment are often disparate. This experiment aimed to reduce this incongruence in forensic anthropological interpretation of burned human remains and implicitly contribute to the development of research methodologies sufficiently robust to withstand forensic scrutiny in the courtroom. We have tested the influence of thermal alteration on pre-existing sharp and blunt trauma on twenty juvenile sheep radii in the laboratory using an automated impact testing system and an electric furnace. The testing conditions simulated a worst-case scenario where remains with pre-existing sharp or blunt trauma were exposed to burning with an intentional vehicular fire scenario in mind. All impact parameters as well as the burning conditions were based on those most commonly encountered in forensic cases and maintained constant throughout the experiment. The results have shown that signatures associated with sharp and blunt force trauma were not masked by heat exposure and highlights the potential for future standardization of fracture analysis in burned bone. Our results further emphasize the recommendation given by other experts on handling, processing and recording burned remains at the crime scene and mortuary.